Relationship Between Nutritional Factors, Sports Practicing and Falls among Elderly People in Baghdad City, Iraq, 2012 - Abdal Qader, Mohammed A.; Amin, Rahmah Mohd.; Shah, Shamsul Azhar; Isa, Zaleha Md.; Ghazi, Hasanain Faisal (Pakistan Journal of Nutrition, 2013)
Ageing of the population is one of the most important demographic facts that came to the foreground in the 21st century. Apart from social and economic problems, the elderly population is very much associated with health problem. Nutrition is an important factor in falls prevention among elderly, as weakness results from a loss of muscle mass and strength, neuromuscular impairment, immobilisation and malnutrition. This study was conducted to assess the relationship between nutritional factors and sport with falls among elderly people in Baghdad city, Iraq. A matched 1:1 community based case-control study involving 716 elderly respondents, recruited randomly from six Non Governmental Organization (NGO) in different areas of Baghdad. Interview questionnaire to each respondent were done accordingly. Food frequency questionnaire were used to obtain the dietary information on weekly frequency of eating certain common food item in Iraq and anthropometric measurement (weight and height) were obtained to get the BMI. The minimum age for cases and controls were 60, the maximum age for cases was 87 years old and 85 years old for controls. Female were predominant than males and were 53.6 and 46.4% respectively. The association between BMI and falls was statistically significant (p = 0.004). Practicing sport or walk exercise was a protective factor for falls. All the micronutrients were significantly associated with falls except for vitamin C. It is concluded that nutrition of the elderly is one of the important risk factors contributing to falls. Elderly with low dietary intake of calcium and vitamin D, phosphorus, Protein and Iron are at risk for falls. Elderly not practicing sport are at higher risk of falls.